INVESTIGATING FORMATIVE EVALUATION IN THE ENGLISH LANGUAGE CLASSROOM OF SECONDAY SCHOOLS IN PAKISTAN: A MIXED-METHOD TECHNIQUE - Mehak Jawed; Sana Bint e Javaid (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the employ of formative assessment in secondary school English lessons in Karachi’s FL classrooms with the goal of learning more about these practices. The research employs a mixed-method retrospective analysis, gathering data from 120 alumni of different secondary schools in Karachi between 2021 and 2020 via questionnaires and a Likert scale. Gaining understanding of the number, type, and significance of assessments they encountered throughout their secondary education is the aim, especially when contrasting formative and summative evaluations for various FL skills and sub skills. The results show that formative assessment is not given enough weight in Karachi’s EFL curriculum. About 20% of students said they had never received formative evaluations in the areas of practical skills, comprehension, and pronunciation. These answers demonstrate how well students comprehend the value of feedback and the consequences of providing it insufficiently. The findings clearly point to the need for improvements in pre-service and in-service teacher training programs as well as a better knowledge and application of formative evaluation in Karachi’s EFL classrooms. By addressing these problems, Karachi, Pakistan’s English language instruction could become much better.